2010
DOI: 10.1016/j.joep.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance targets, effort and risk-taking

Abstract: Growing economic and psychological evidence documents e¤ects of target setting on levels of e¤ort and risk-taking, even in the absence of a monetary reward for attaining the target. I explore a principal-agent environment in which the principal sets the agent a performance target, and the agent's intrinsic motivation to work is in ‡uenced by their performance relative to the target. When the agent has prospect theory preferences relative to the target I show that a performance target can induce greater e¤ort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Innovation prizes (often referred to as ‘inducement prizes’) are a special type of award that seeks to promote new ways of overcoming economic and social problems. A monetary sum is offered to that person or group of persons finding a solution to a well‐specified problem (on the motivational effects of nonmonetary targets, see Rablen, ). It has been empirically shown that the winners of science problem‐solving contests are often people whose field of technical expertise is distant from the field in which the problem originated (Jeppesen and Lakhani, ).…”
Section: Types Of Awardsmentioning
confidence: 99%
“…Innovation prizes (often referred to as ‘inducement prizes’) are a special type of award that seeks to promote new ways of overcoming economic and social problems. A monetary sum is offered to that person or group of persons finding a solution to a well‐specified problem (on the motivational effects of nonmonetary targets, see Rablen, ). It has been empirically shown that the winners of science problem‐solving contests are often people whose field of technical expertise is distant from the field in which the problem originated (Jeppesen and Lakhani, ).…”
Section: Types Of Awardsmentioning
confidence: 99%
“…The deflated performance manipulation behavior can help the private sector use the unreported surplus performance to smooth performance in the next period, so as to guarantee seemly performance growth. Rablen (2010) employed goal-setting theory to explain why agents tend to take the risk to attain a high target. It was reported that agent would reduce their real performance in various ways, for example, reducing investments (Eldenburg et al, 2011), allowing for price discounts (Roychowdhury, 2006), because deflated performance manipulation is concealed and is challenging to be detected (Bouwens & Kroos, 2011).…”
Section: Ratchet Effectmentioning
confidence: 99%
“…It is because the latter can help store managers use the unreported surplus performance to smooth performance in the next period, for example, earnings management [1,[19][20][21], so as to guarantee seemly performance growth. Goal-setting theory provides evidence to explain the reason that managers tend to take risk to attain a high target [22]. Leone and Rock [23] suggested that managers are promoted to manipulate reported earnings downward by accruals.…”
Section: Literature Reviewmentioning
confidence: 99%